The importance of being seven ebook - McCall Smith, Alexander (44 Scotland Street, 2012)
44 SCOTLAND STREET - Book 6 The residents and neighbors of 44 Scotland Street and the city of Edinburgh come to vivid life in these gently satirical, wonderfully perceptive serial novels, featuring six-year-old Bertie, a remarkably precocious boy—just ask his mother.     The great city of Edinburgh is renowned for its impeccable restraint, so how, then, did the extended family of 44 Scotland Street come to be trembling on the brink of reckless self-indulgence? After seven years and five books, Bertie is—finally!—about to turn seven. But one afternoon he mislays his meddling mother Irene, and learns a valuable lesson: wish-fulfillment can be a dangerous business. Angus and Domenica contemplate whether to give in to romance on holiday in Italy, and even usually down-to-earth Big Lou is overheard discussing cosmetic surgery. Funny, warm, and heartfelt as ever,  The Importance of Being Seven  offers fresh and wise insights into philosophy and fraternity among Edinburgh's most lovable residents.